STUDI KONSEP PENDIDIK DAN PESERTA DIDIK : PEMIKIRAN ABUDDIN NATA DAN ZAKIAH DARADJAT - Farichah, Eneng (STAI Darul Qalam Tangerang, 2024)
This study aims to determine the concept of educators and students and the purpose of this study is to determine how the concept of educators and students think of Abuddin Nata and Zakiah Daradjat. This study is a library research (library research). The primary data sources are the book